Nursing performance in assistance to patients with self-infringement in emergency and emergency (Research, Society and Development, 2022)
This study aims to describe the role of nurses in caring for patients with self-harm by suicidal behavior in Urgent and Emergency units. This is an integrative review study carried out in the Virtual Health Library, American Medicine Library, Scientific Electronic Library Online, Scopus and Academic Search Premier databases. A total of 2,316 articles were found, of which 13 studies were selected for final analysis. As a result of the research, the categories emerged: risk classification, clinical care, psychological care, family care, referrals and discharge planning, prevention and training of the multiprofessional/nursing team were the main actions developed by nurses for patients with self-harm. The nurse who works in the emergency room and is responsible for the care of patients with self-harm needs to have scientific and practical knowledge, aiming to make quick and concrete decisions, convey safety to the entire team and mainly reduce the risks that threaten the patient's life.